Digital Humanities in the Covid Era: The Perspective of a Historian of Modern Indonesia from Northern Japan (History Department, Semarang State University and Historian Society of Indonesia, 2022)
The covid-19 era has changed the world, including more “open access” publications, the increasing importance of digital research materials, and engagement in digital interactions of increased importance in the humanities. Perspectives of isolated scholars, in this case, working on the history of Indonesia during World War II from a small national university in a remote city in northern Japan, provide an essential perspective on conducting research and creating digital archives. Far closer to Indonesian students and researchers than researchers in major universities in the West, such practical perspectives are urgently needed to achieve the full potential of digital humanities. Some archives and public library collections have developed digital collections for readers and researchers, however smaller collections of materials made by scholars in the course of their research are also of significant importance but present a large number of unique problems, including dependence on low-budget efforts by individual scholars in their “spare time” to do all the planning and digitizing of their research materials. A coordinated effort by a group of scholars in northern Japan to digitize materials on Indonesian history is making progress but faces different problems than those of large institutions. These problems include long-term support, determining and coding materials for their accessibility, depending on the nature of the material and the rights involved. None-the-less, it is hoped that innovative collaboration will allow some of these materials to be made available to the general public and outside researchers while minimizing the disadvantages. Era covid-19 telah membawa perubahan bagi dunia, termasuk lebih banyak publikasi “akses terbuka”, semakin pentingnya bahan penelitian digital, dan keterlibatan dalam interaksi digital yang semakin penting dalam humaniora. Perspektif sarjana yang terisolasi, dalam hal ini, bekerja pada sejarah Indonesia selama Perang Dunia II dari sebuah universitas nasional kecil di kota terpencil di Jepang utara, memberikan perspektif penting dalam melakukan penelitian dan membuat arsip digital. Jauh lebih dekat dengan mahasiswa dan peneliti Indonesia daripada peneliti di universitas-universitas besar di Barat, perspektif praktis seperti itu sangat dibutuhkan untuk mencapai potensi penuh humaniora digital. Sejumlah arsip dan koleksi perpustakaan umum telah mengembangkan koleksi digital untuk pembaca dan peneliti, namun koleksi bahan yang lebih kecil yang dibuat oleh para sarjana dalam perjalanan penelitian mereka juga sangat penting tetapi menghadirkan sejumlah besar masalah unik, termasuk ketergantungan pada rendahnya sumber daya. upaya anggaran oleh para sarjana individu di